CD146+ mesenchymal stem cells display greater therapeutic potential than CD146– cells for treating collagen-induced arthritis in mice. Issue 1 (December 2016) - Wu, Cheng-Chi; Liu, Fei-Lan; Sytwu, Huey-Kang; Tsai, Chang-Youh; Chang, Deh-Ming
Abstract Background The characteristics and therapeutic potential of subtypes of mesenchymal stem cells (MSCs) are largely unknown. In this study, CD146+ and CD146– MSCs were separated from human umbilical cords, and their effects on regulatory T cells (Tregs), Th17 cells, chondrogenesis, and osteogenesis were investigated. Methods Flow cytometry was used to quantify IL-6 and TGF-β1 expressed on CD146+ and CD146– MSCs. The therapeutic potential of both subpopulations was determined by measuring the clinical score and joint histology after intra-articular (IA) transfer of the cells into mice with collagen-induced arthritis (CIA). Results Compared with CD146– MSCs, CD146+ MSCs expressed less IL-6 and had a significantly greater effect on chondrogenesis. After T lymphocyte activation, Th17 cells were activated when exposed to CD146– cells but not when exposed to CD146+ cells bothin vitro and in vivo . IA injection of CD146+ MSCs attenuated the progression of CIA. Immunohistochemistry showed that only HLA-A+ CD146+ cells were detected in the cartilage of CIA mice. These cells may help preserve proteoglycan expression. Conclusions This study suggests that CD146+ cells have greater potency than CD146– cells for cartilage protection and can suppress Th17 cell activation. These data suggest a potential therapeutic application for CD146+ cells in treating inflammatory arthritis.